PERAN PEMERINTAH DAERAH KABUPATEN ROKAN HULU DALAM PEMERATAAN LISTRIK DI KECAMATAN TAMBUSAI UTARA TAHUN 2015 - Salty, Ria Erica; Yusri, Ali (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Rokan Hulu regency consists of 16 districts and 157 villages / wards, from the District 16 is 1 sub-district which is very minimal in meeting the electricity needs of the District of North Tambusai. To meet the demand for electricity in addition to coming from PLN, the public use of diesel engines, generators, and kerosene. To meet the needs of electricity evenly local governments can not be done in full because of the limited authority of the regions in the provision and management of electricity. However, local governments are still trying to supply power to all villages with cooperation SOEs namely PLN and the private sector in providing rural electricity. These efforts are supported by the development of road infrastructure of local governments as access to entire villages that have not been electricity. This study aims to determine the role of local government's role in meeting the Rokan Hulu electrical equalization and constraints of local government's role in meeting the Rokan Hulu kebtuhan electrical equalization. This study uses qualitative research methods with descriptive research, which can be interpreted as a problem-solving process was investigated by describing the state of the research subjects were based on the facts that appear during the study were then followed by the popularity of existing theories. Based on the results of this study concluded that the electricity problems that occurred in the district of North Tambusai has not been resolved to the fullest. The role of government in meeting the electricity needs of the community in the District Tambusai new North evident from developments in the electricity grid and already there are 2 villages that have electricity from PLN, aid ginset from the government for each village, development cooperation power biogas (PLTBg), and the form bring in new investors to manage and develop the electric power biogas derived from palm oil that is still not a clear sign of the start of construction. Keywords: Roles, Power Fulfillment